(The Prospect of The Use of Activated Carbon in Industry) - HG Pohan (Warta Industri Hasil Pertanian, 1993)
Actived carbon is an amorphous or microcrystalline from carbon which have very large surface area,ranging from 300-2000 meter/gr.There are two process of activation,chemical and physical process.The quality of activated carbon depend on their raw material and activation method.Activated carbon are laregely used in multivarious industry i.e.food and beverage,pharmaceutical,waste treatment and chemical industries.